Inflammasome, T Lymphocytes and Innate-Adaptive Immunity Crosstalk: Role in Cardiovascular Disease and Therapeutic Perspectives - Pedicino, Daniela; Giglio, Ada Francesca; Ruggio, Aureliano; Massaro, Gianluca; D'Aiello, Alessia; Trotta, Francesco; Lucci, Claudia; Graziani, Francesca; Biasucci, Luigi Marzio; Crea, Filippo; Liuzzo, Giovanna (Thrombosis and Haemostasis, 2018)
Over the past few decades, lot of evidences have shown atherosclerosis as a chronic progressive disease with an exquisite inflammatory feature. More recently, the role of innate immune response in the onset and progression of coronary artery disease (CAD) and an adaptive immunity imbalance, mostly involving T cell sub-sets, have been documented. Therefore, like in many other inflammatory and autoimmune disorders, an altered innate-adaptive immunity crosstalk could represent the key of the inflammatory burden leading to atherosclerotic plaque formation and progression and to the breakdown of plaque stability. In this review, we will address the role of inflammasome in innate immunity and in the imbalance of adaptive immunity. We will discuss how this altered immune crosstalk is related to CAD onset and progression. We will also discuss how unravelling the key molecular mechanisms is of paramount importance in the development of therapeutic tools to delay the chronic progression and prevent the acute destabilization of atherosclerotic plaque.
Keywords: precision medicine; inflammasome; innate immunity; adaptive immunity; coronary artery disease; acute coronary syndromes